The Palestinian-Israeli Conflict in the Memory of the Past the Jewish Nation: From Holocaust to Holocaust - Mubarok, Fahmi; Meidina, Ahmad Rezy (Indonesian Academy of Social and Religious Research (IASRR), 2024)
This paper explores the dynamics of the Palestinian-Israeli conflict through the perspective of Jewish history and collective memory, with a particular focus on the Holocaust as a point of departure. Through a history of civilization approach and collective memory analysis, this paper explores how the traumatic experience of the Holocaust has shaped the identity, politics and narratives of the Jewish people to influence their views on the ongoing conflict in the Middle East. It reveals how the memory of the Holocaust is not only an integral part of Jewish identity but also plays a role in shaping the policies and strategies adopted by the state of Israel. Holocaust memory is often used to justify defensive and offensive actions to sustain the Jewish state amidst external and internal threats. In this context, the